(3GOGQI GdehGQOs - (3cGXe(B, (3MehO NVjQs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2001)
(3GdeaGgje GdGSGSjI dGOGQI GdTQGA (B2- (3GdGUhd GdYdejI dGOGQI GdTQGA JNWjW GdTQGA (B3- (3JfajP GdTQGA (B4-(3Jbjje GdTQGA (B5- (3JNWjW GdeNRhf (B6- (3GLQGAGJ GdJNRjf (B7- (3GdQbGHI Ydi GdeNRhf (B.s
Keywords: (3EOGQI GdGYeGds; (3GOGQIs; (3GOGQI GdTQGAs; (3GOGQI GdehGOs; (3ehGQOs